Incorporation of Nutritionally Important Fatty Acids into Eggs and Evaluation of "Bio-Omega-3" Eggs in Humans with Moderate Hypercholesterolemia - Imran, Muhammad; Anjum, Faqir M.; Butt, Masood S.; Chatha, Zia A. (Pakistan Journal of Nutrition, 2013)
This study focuses on impact of consuming "Bio-omega-3" eggs on serum lipids profile of humans with a view to improve the nutrient intake of consumers in a palatable and acceptable commodity. Twenty four statin-treated volunteers with moderate hypercholesterolemia ranging in age from 25-40 years old having no diagnosed heart disease were selected from the community. Average increment in HDL-cholesterol (by 10.27%) and decrease in serum lipids concentration (by 14.18%) without significantly altering the circulating total cholesterol levels was found in human subjects after consumption of omega-3 fatty acids-enriched eggs as compared to control eggs. LDL-cholesterol, total protein, albumin and glucose concentration remained unchanged after consumption of experimental eggs (p<0.05). The results of the present study demonstrated that eggs that are enriched with omega-3 fatty acids may offer the public an alternative. With such modifications, the omega-3 fatty acids-enriched eggs may be more healthful than the conventional eggs.